Button batteries in the ear, nose and throat: a novel survey of knowledge of UK advanced nurse practitioners. (23rd June 2022) - Lotfallah, Andrew; Al-Hity, Shams; Rodrigues, Rodney; Hamzah, Aisha; Kumar, Ravi; Darr, Adnan
Abstract : Background: Button battery (BB) impaction in the ear, nose and throat can result in significant morbidity. Advanced nurse practitioners (ANPs) are increasingly responsible for initial patient assessment and prompt escalation to otolaryngologists for definitive management. Aim: Our novel national study aimed to assess ANPs' knowledge with respect to the assessment and management of patients with BBs in the ear, nose and throat. Method: A national 13-point survey was disseminated among ANPs over a 2-week period. Knowledge was assessed through eight multiple choice questions with a maximum attainable score of 21. Findings: A total of 242 responses were analysed. Knowledge deficits were identified in all domains (mean overall score 8.5/21), including presenting clinical features, preliminary investigations and intervention strategies. The overwhelming majority of respondents (97%; n =234) advocated for further training. Conclusion: A need for further education has been highlighted by this surveyed cohort of ANPs. Implementation of standardised protocols, virtual resources and simulation platforms may address knowledge deficits.